Kinetics of hydroformylation of camphene using rhodium-phosphite catalyst - Pagar, Nitin S.; Rajurkar, Kalpendra B.; Deshpande, Raj M. (International Journal of Chemical Kinetics, 2020)
Kinetics of hydroformylation of camphene was investigated in the presence of [Rh(CO)(2)(acac)]/P(OPh)(3) catalyst in a temperature range of 363-383 K. The influence of parameters such as stirring speed, camphene, catalyst, ligand concentrations, and partial pressures of H-2 and CO on the activity and selectivity of the catalyst has been studied. The rate showed a first-order dependence with respect to catalyst and camphene concentrations. The effect of partial pressure of hydrogen showed fractional order dependence. The plots of rate versus excess ligand, that is, (P(OPh)(3)) concentration and rate versus CO partial pressure passed through maxima and showed typical substrate/ligand inhibited kinetics. An empirical rate equation has been proposed and found to be in good agreement with the observed rate data. The kinetic parameters and activation energy were also evaluated.
Keywords: camphene; homogeneous; Hydroformylation; kinetics; rhodium-phosphite